EXPRESSIVE ACTS USED BY THE MAIN CHARACTER IN LIFE OF PI FILM - LATUMAELISSA, KHRISNA CAPELLA UTAMA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Speech Acts, Illocutionary Acts, Expressive Acts. Language is a mediumto deliver message among humans to reach understanding to each other. Expressing feeling and emotion are also included into language’s function performed in daily conversation. Viewed from the Speech Acts theory, expressing feeling and emotion is included into expressive act. Expressive acts are the ones indicating psychological states of the speaker which can be statements of thanking, apologizing, welcoming, congratulating, and so on. Dealing with this, the writer conducted a research about expressive actsof the main character’s utterances in Life of Pi film. There are two problems to be solved; (1) what are the types of expressive acts in Life of Pi film, and (2) what are the functions of expressive acts in Life of Pi film.This research uses qualitative method because the analysis is in the form of description. Then, the research is conducted through documentary analysis since Pi’sutterances are in textual form of film script containing expressive acts. The result ofthe research shows there are four types of expressive acts used by Pi in his utterances, namely (1) acts of thanking, (2) acts of apologizing, (3) acts of congratulating, and (4) acts of welcoming. There are also seven functions of expressive acts in Pi’s utterances, including (1) to show gratitude, (2) to show regret, (3) to avoid conflict, (4) to show acceptance, (5) to reveal guilty feeling, (6) to show frustration, and (7) to show appreciation.The findings of this research shows that the types of expressive acts used mostly in the main character’s utterances is acts of apologizing followed by acts of thanking. Meanwhile, the functions of expressive acts are various caused by the situations around the utterances. The writer wants to give suggestion to the next researchers who are interested in conducting thesis in the same field to conduct a research about expressive acts from other sources, such as reality shows, interviews and serial TV shows to extend the theory of expressive acts. At last, the writer hopes this research can be a reference about expressive acts.